Third Five-Year Plan of North Kanara District Government of Mysore - Planning Commission (Planning Commission)
Taluka Boundaries. Taluka Headquarters. Block Boundaries. Block Headquarters. Municipal Towns other than those mentioned above. National and State Highways, Railways and Rivers. Economic Survey of the District (narrative) indicating.
Government of Mysore